Pengetahuan dan Sikap Ibu Hamil Trimester III tentang anemia defisiensi zat besi: Indonesia - Friska Margareth Parapat (Universitas Prima Indonesia, 2020)
Background: the function of red blood cells provides oxygen to all body tissues. The high maternal mortality rate in Indonesia is one of the causes is the low consumption of iron during pregnancy, so there are many cases of iron nutrition anemia. Based on Basic Health Research (RISKESDAS) the percentage of anemia in pregnant women in Indonesia is 24.5%. The purpose of this study was to determine the extent of knowledge and attitudes of pregnant women towards the prevention of iron deficiency anemia. Research methods: the method used is descriptive. The number of samples in this study were Trimester III pregnant women, amounting to 50 people. Sampling was taken with a total sampling technique. The research was conducted at the Cahaya Clinic, Pulo Brayan Darat Sub-District, East Medan District. Results: In terms of knowledge on the prevention of iron deficiency anemia obtained from 50 pregnant women in the Light Clinic as many as 26 people (52%) had sufficient knowledge, had 14 people (28%), and 10 people (20%) lacked knowledge. Based on the attitude of Trimester III pregnant women as many as 43 people (86%) are behaving well, and 7 people (14%) are acting less on matters relating to the prevention of iron deficiency anemia. Conclusion: this study needs to increase the intake of iron nutrition of pregnant women based on a healthy and balanced diet (4 healthy 5 perfect). Keywords: Knowledge, attitude, pregnant mother,trimester III iron deficiency anemia